Cardiac disease in pregnancy. Issue 1 (May 2022) - Rex, Steffen; Devroe, Sarah
Abstract : In the developed world, cardiovascular disease has become the most frequent cause of death during pregnancy and postpartum, outnumbering by far obstetric causes of death such as bleeding or thromboembolism. Many factors contribute to this phenomenon, including an increasing age of pregnant women, co-morbidities, and an unhealthy lifestyle. The cardiovascular system is not only significantly challenged by physiological alterations in pregnancy but also by obstetric medication. Depending upon the severity of the underlying condition, pregnant women with cardiovascular disease should be managed by a multidisciplinary heart team in which anaesthesiologists play an important role. Profound knowledge of the cardiac pathophysiology is a prerequisite for the successful anaesthesiologic management of pregnant patients with cardiovascular disease. As there is no difference in general and regional anaesthesia regarding maternal outcomes, neuraxial anaesthesia using incremental techniques should be preferred for labour and (caesarean) delivery if not contraindicated by non-cardiac issues.